Optimizing Cardiac Out-Put to Increase Cerebral Penumbral Perfusion in Large Middle Cerebral Artery Ischemic Lesion—OPTIMAL Study - Fuhrer, Hannah; Günther, Albrecht; Zinke, Jan; Niesen, Wolf-Dirk (Frontiers in Neurology, 2017)
Introduction In unsuccessful vessel recanalization clinical outcome of acute stroke patients depends on early improvement of penumbral perfusion. So far, mean arterial blood pressure (MAP) is the target hemodynamic parameter. However, the correlations of MAP to cardiac output (CO) and cerebral perfusion are volume state-dependent. In severe subarachnoid hemorrhage optimizing CO lead to a reduction of delayed ischemic neurological deficits and improvement of clinical outcome. This study aims to investigate the effect of standard versus advanced cardiac monitoring with optimization of CO on the clinical outcome in patients with large ischemic stroke. Methods and analysis The OPTIMAL-study is a prospective, multicenter, open, into two arms (1:1) randomized, controlled trial. Sample size estimate: Sample sizes of 150 for each treatment group (300 in total) ensure an 80% power to detect a difference of 16% of a dichotomized level of functional clinical outcome at 3 months at a significance level of 0.05. Study outcomes: The primary end-point is the functional outcome at 3 months. The secondary end-points include functional outcome at 6 months follow-up, and complications related to hemodynamic monitoring and therapies. Discussion The results of this trial will provide data on the safety and efficacy of advanced hemodynamic monitoring on clinical outcome. Ethics and dissemination The trial was approved by the leading ethics committee of Freiburg University, Germany (438/14, 2015) and the local ethics committees of the participating centers. The study is performed in accordance with the Declaration of Helsinki and the guidelines of Good Clinical Practice. It is registered in the German Clinical Trial register (DRKS; DRKS00007805). Dissemination will include submission to peer-reviewed professional journals and presentation at congresses. Hemodynamic monitoring may be altered in a specific stroke patient cohort if the study shows that advanced monitoring is safe and improves the functional outcome.